STUDI KASUS GANGGUAN PEMUSATAN PERHATIAN ANAK USIA 6 TAHUN DI TAMAN KANAK-KANAK AISYIYAH 29 PADANG - Rafidah, Fhany; Mahyuddin, Nenny (IAIIG Cilacap, 2019)
Parents and teacher have an important role in chlidrens development. Many childrens behavior are misunderstood so that they give the child a naughty label. Actually the child only needs to get attention fron the teacher or parents. Because of this luck of awareness, the researchers were interested in conducting research on case study of attention deficit disorder in children aged 6 years at TK Aisyiyah 29 Padang. this study describes the behavior of children who experience impaired concentration and efforts of the teacher in dealing with it. This type of research is qualitative research with a case study approach. The research informan were clas teachers and parents of children at Aisyiyah 29 kindergarten in Padang. Data collection techniques in the form of grouping, direct interpretation, setting patterns and generalizations. While the technique of validating data is an extention of obsevation, increasing perseverance and triangulation. The results of study showed that the behavior of children with concentration problems in Aisyiyah 29 padang kindergarten and the teachers efforts in dealing with it. Behavior that is shown by children such as: 1) behavior less attention: not playing attention when talking to other people, difficulty maintaining attention to the task or activity, making mistakes in the job and often losing goods; 2) easily disturbed: easily disturbed stimulus that is not related and easily diaturbed to friends around; 3) obey the heart: not following orders, failing to complete tasks and rejecting ongoing and complicated tasks. The findings are supported by relevant theories and expert opinions. Some of the efforts made by teachers in dealing with children with attention deficiencies such as the determination of sitting position im the class that confronts the teacher of the position of his own seat, the teacher reprimands the child, the teacher scares the child, the teacher support the child when studying/activuties and discusses with parents.